Content-Based Image Retrieval Using Extended Local Tetra Patterns - Choudhary, Deepika; Amit; malik, Suraj; Singh, Pankaj Pratap (International Journal of Computer Sciences and Engineering, 2019)
In this modern world, finding the desired image from huge databases has been a vital problem. Content Based Image Retrieval is an efficient method to do this. Many textures based CBIR methods have been proposed so far, for better and efficient image retrieval. We aim to give a better image retrieval method by extending the Local Tetra Patterns (LTrP) for CBIR using texture classification by using extended version of LTrP. These features give additional information about the color and rotational invariance. So an improvement in the efficiency of image retrieval using CBIR is expected.